use identities to simplify expression

the equation must be in the form (sec x/tan x)^2-(1/(tan x)^2)

(sec x/tan x)^2-(1/(tan x)^2)=(sec x)^2/(tan x)^2-1/(tan x)^2=(1/(tan x)^2)*((sec x)^2-1)=(1/(tan x)^2)*((1/(cos x)^2)-1)

=(1/(tan x)^2)*((1-(cos x)^2)/(cos x)^2)=(1/(tan x)^2)*((sin x)^2/(cos x)^2)=(1/(tan x)^2)*(tan x)^2=

=(tan x)^2/(tan x)^2=1

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up